A novel fed-batch strategy enhances lipid and astaxanthin productivity without compromising biomass of Chromochloris zofingiensis. (July 2020) - Sun, Han; Ren, Yuanyuan; Lao, Yongmin; Li, Xiaojie; Chen, Feng
Graphical abstract: Highlights: Fed-batch strategy increased 41.5% lipid productivity without compromising biomass. Carbon dependent kinetics under stress conferred cells with a higher biomass. Central carbon metabolism offered energy and carbon availability for lipid synthesis. Sufficient precursor and active synthetic pathway promoted lipid content. Fed-batch strategy was attractive by understanding lipid metabolism in detail. Abstract: To improve lipid and astaxanthin productivity without compromising biomass during the whole cultivation period, carbon-dependent kinetics involving nitrogen stress was applied under excess light to elevate intracellular carbon availability and metabolic activity of Chromochloris zofingiensis . Results suggested that fed-batch strategy proposed could increase lipid and astaxanthin productivity to 457.1 and 2.0 mg L −1  d −1, respectively. Biomass productivity at 1084.3 mg L −1  d −1 was comparable with that under suitable condition. Then 13 C tracer-based metabolic flux analysis ( 13 C-MFA) demonstrated that central carbon metabolism provided ATP, NADPH and carbon availability for lipid biosynthesis during the strategy. In combination with targeted metabolite analysis, 13 C-MFA revealed that the strategy improved precursor content for lipid biosynthesis and elevated path rate to synthesize C16:0 and C18:0. The enhanced lipid content potentially accounted for the high biomass productivity. Therefore, comprehensively understanding relationships between carbon availability and carbon conversion could precisely design strategy for productivity improvements during cultivation.